DEFENSE MECHANISM IN SIDNEY SHELDON’S THE STARS SHINE DOWN: A PSYCHOANALYTIC APPROACH - Cahyaningrum, Evi (2010)

(untitled)
The major problem of this study is how anxiety is reflected in the major character’s personality. The aim of this study is to analyze Sidney Sheldon’s The Stars Shine Down and the personality of the major character based on Psychoanalytic Approach. This study focuses on the major character, namely Lara Cameron. This study belongs to qualitative study. In this method, the writer uses two data source. The primary data source object of the study are, the novel The Stars Shine Down it self. Meanwhile the secondary data sources are any books of literature and psychology related to this study. The writer collects the data from both primary and secondary data source in a short of document evidence. Based on the analysis, the outcome of this study shows that the problem of major character encounters causes the conflicts of her mental condition. Then, it develops to become anxiety and influences her to do some ways to solve the problem that she faces from it. She also uses some ego defense mechanism to overcome the anxiety that appears in her personality. Finally, her ways to overcome the anxiety is successful and the problems that she faces cam loose one by one. Lately, her personality changes become more confident and brave to face the fact that she is the only woman in the real estate business with all of the obstacles.